Scientific explanation of composition of acidophilic-whey ice cream, enriched with protein - Polishchuk, Galyna; Kochubei-Lytvynenko, Oksana; Osmak (Fedchenko), Tetiana; Bandura (Kuzmyk), Uliana; Bass, Oksana; Mykhalevych, Artur; Sapiga, Victoria (My University, 2021)
The work is devoted to solving the actual problem of the dairy industry - complex processing of food raw materials, expanding the range of dairy and milk-containing products of high nutritional value due to enrichment of protein, pro- and prebiotics, rational use of production resources by reducing the the technological process duration. The aim of the research is to substantiate the composition of a new type of acidophilic-whey ice cream of high nutritional value due to enrichment with a complex of proteins, probiotic sourdough and pectin-containing vegetable paste.
Keywords: serum; acidophilus ice cream; acidophilus ice cream; ацидофільне морозиво; сироватка; комбіновані молочні продукти; кафедра технології молока і молочних продуктів